Поселення доби середньої – пізньої бронзи Алуштинського регіону - Теліженко, С.А.; Яніш, Є.Ю. (Матеріали та дослідження з археології Східної України, 2013)
Публікацію присвячено аналізу матеріальної культури поселень епохи середньої та пізньої бронзи – Алігор та Чангаринин Дересі, досліджених на території м. Алушта. Статья вводит в научный оборот материалы двух памятников эпохи средней и поздней бронзы – Алигор и Чангарынын Дереси, которые исследовались на территории Алуштинского региона. Местонахождение Алигор, судя по характерным особенностям артефактов (керамики и отдельных категорий кремневого инвентаря), соотносится с памятниками эпохи средней бронзы, расположенными в восточной и юго-восточной частях Крымского полуострова. Поселение Чангарынын Дереси представляет собой памятник переходного периода – от финальной бронзы к раннему железному веку. This publication analyzes the materials of the Middle Bronze - Late Bronze Age settlements Aligor and Changarynyn Deresi (Southern coast of Crimea). According to the characteristic features of artifacts (pottery and some flints tools) Aligor site correlated with the Middle Bronze Age sites of the, eastern and south-eastern parts of the Crimean peninsula. Changarynyn Deresi is a settlement of the transition period - from the Final Bronze Age to the Early Iron Age.